Fragments of a Writer’s Mind: Virginia Woolf in Her Own Words - Zeitoun, Baheya (AUC Knowledge Fountain, 2023)
This thesis provides a thematic reading of select autobiographical and theoretical works by Virginia Woolf. It utilizes Deleuze and Guattari’s philosophy of the rhizome as a methodological framework. The rhizome does not have a hierarchal structure but is rather interconnected. In the same way, the chapters interweave the multi-disciplinary theoretical approaches to connect the disparate factions of the modernist writer’s mind and life. The early twentieth century saw the rise of post-suffrage writers with narratives that diverged from male-centric values. Woolf is one of the writers who makes a clear distinction between male and female values by championing women’s experiences and struggles. She argues for female economic independence, through education and employment opportunities. In addition, she emphasizes the importance of female intellectual production to bridge the gap between men’s and women’s voices in history. The theme of mental health is discussed by analyzing Woolf’s fiction and non-fiction writings on the topic. Given her struggles with manic depressive disorder, known contemporarily as bipolar disorder (BD), she also serves as a case study for the condition and how it is linked to creativity. By following her writing style and feminist views on her society, light is shed on mental health struggles in the early twentieth century and compared to contemporary theories. As Woolf lived through a tumultuous period of British history, she witnessed the rise of the emotionally expressive modernist movement and became one of its most prominent literary figures. The movement utilized a literary device known as stream-of-consciousness writing; an approach to consciousness proposed by American psychologist William James. Thus, psychology and mental health were vital to her use of language and central to her written works, which provided insight into her psyche.